ANALYSIS OF CONSUMER BEHAVIOR IN CHOOSING ATTRIBUTES OF LARGE RED CHILI WITH A CONJOINT ANALYSIS APPROACH - Idham Parhanudin; Zumi Saidah (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2025)
Large red chili is a high value horticultural commodity that plays a vital role in meeting Indonesia's food demands, both for domestic consumption and industrial purposes. The high production rate of red chili corresponds with increasing consumer needs, influenced by diverse preferences that shape purchasing behavior, perceptions, and decisions. This study aims to identify the attributes most considered by consumers and analyze the combinations of large red chili attributes based on consumer preferences in Bandung City. A quantitative descriptive method was employed using questionnaires, with perceptual mapping applied to evaluate consumer perceptions and conjoint analysis used to determine consumer preferences. The findings reveal that consumer perceptions of price and freshness attributes tend to be neutral, with average scores of 3 on a Likert scale. Meanwhile, shelf life, taste, and color are perceived positively, with average scores of 4. Regarding preferences, consumers prioritize a combination of affordable prices (<Rp20,000.00/kg), high shelf life (5–6 days), very fresh conditions, mildly spicy taste, and bright red color. Among all attributes, freshness is identified as the most critical factor based on its relative importance in shaping consumer preferences.